Trade-offs between management and conservation for the provision of ecosystem services in the southern Patagonian forests. - Rosas, Yamina Micaela (2020)
Forests provide critical ecosystem services for human well-being; however, some ecosystem services are more valued (e.g. provisioning services) than others (e.g. regulating or supporting services). Temperate regions contain several forests affected by humans, mainly with regard to ecosystem services and biodiversity. This chapter focuses on Nothofagus forests in southern Patagonia. It analyzes potential trade-offs between ecosystem services and biodiversity, and how new silvicultural approaches (such as silvopastoral and variable retention harvesting) allow multi-objective management at the landscape level. The authors first discuss forest ecosystem service characterization. Further sections are included on the provision of forest ecosystem services in southern Patagonia and developing strategies of sustainable forest management. The chapter closes with an overview of forest ecosystem services in a changing world. The authors conclude that future proposals (such as land-sharing) will require fewer trade-offs and promote positive synergies within the provision of ecosystem services, generating more resilient alternatives that can mitigate potential climate change effects.